Outcomes between different validated questionnaires to assess the level of physical activity in cardiac patients adhering to a rehabilitation program - Gomes, Rayana Loch [UNESP]; Lopes, Jaqueline Santos Silva; de Marco, Rafael Luiz [UNESP]; de Almeida, Camila Balsamo Gardim [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Lorençoni, Roselene Modolo Regueiro [UNESP] (FapUNIFESP (SciELO), 2022)
Introduction: The International Physical Activity Questionnaire (IPAQ) and Baecke inventory are commonly used in cardiovascular rehabilitation routines. Thus, it is understood that investigations on the equivalence of outcomes between these two tools may be relevant to measure the magnitude of possible reproducibility and correlations between them. Objective: To compare in cardiac patients the level of physical activity obtained through the IPAQ and Baecke inventory and correlate outcomes obtained with a 6-minute walk test. Methods: In total, 65 heart disease patients included in a cardiovascular rehabilitation program (40 male and 25 female) were included, with a mean age of 65.8 ± 10.5 years. The data were obtained from the application of a standardized form, containing the proposed study objects, which were the IPAQ and Baecke inventory. In addition, data regarding anthropometric measurements (body mass, height, and body mass index - BMI), waist-to-hip ratio, blood pressure, and performance in the 6-minute walk test were measured. Results: The main outcomes refer to the weak association between the instruments evaluated, which showed a strong relationship only between free time physical activity (r = 1), while in the other categories and when compared to the 6-minute walk test, the verified agreement was not significant. Conclusion: The questionnaires are strongly equivalent only for free time physical activity, in the other categories and when compared to the 6-minute walk test, the agreement was not significant. Thus, based on the results, implementation in clinical practice considering the use of these tools with equivalence is not recommended
Desfechos entre diferentes questionários validados para a avaliação do nível de atividade física em cardiopatas adeptos a um programa de reabilitação
Keywords: Cardiac rehabilitation; Cardiorespiratory fitness; Physical exercise; Physiotherapy; Risk factors for heart disease